2017
DOI: 10.5138/09750215.2147
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory aspects of medical devices in India

Abstract: <p>Today millions of patients depend on medical device based treatment for the management and diagnose of several diseases. Quality and safety of device is depends upon the regulatory guidelines. Medical device manufacturing in India should be taken seriously due to large population and the potential severity of the consequences of introducing inferior and unsafe products to the market-place. Therefore a law containing adequate guidelines of rules and regulations are required for monitoring the entry of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Classification and regulation of surgical devices is controlled by the Health Ministry of India (part of the Indian Government) [36] , [37] . The manufacturer’s regulatory team identified that the RAIS system is considered as a Class-A device (Low-risk surgical instrument) and worked with the Design Team to compile the requisite documentation.…”
Section: Resultsmentioning
confidence: 99%
“…Classification and regulation of surgical devices is controlled by the Health Ministry of India (part of the Indian Government) [36] , [37] . The manufacturer’s regulatory team identified that the RAIS system is considered as a Class-A device (Low-risk surgical instrument) and worked with the Design Team to compile the requisite documentation.…”
Section: Resultsmentioning
confidence: 99%
“…In India nowadays, CDSCO is the sole regulatory body governing rules and regulations for medical devices. It from time to time frames and amends the law to guarantee safety to public health [16].…”
Section: Regulatory Aspectsmentioning
confidence: 99%
“…We will compare the medical device rules in India, Europe (MDR), and the USA, highlighting the need for harmonization and the steps involved in obtaining licenses to manufacture medical devices. 11,12 Numerous countries encounter difficulties in obtaining appropriate high-quality medical devices and equipment tailored to their unique epidemiological needs. This challenge is particularly notable in developing nations, where health technology assessments and minimal regulatory oversight are scarce to prevent the importation or use of inferior devices.…”
mentioning
confidence: 99%